Communication studies - Marsen, Sky (Palgrave macmillan, 2006)
This is arguably the first communications textbook to delve into the "real world" of communications. Going beyond the simply theoretical, "Communication Studies" presents the actual challenges of the various industry strata. In the competitive businesses of communications, it's critical that the student/reader know what to expect.